Penerapan Media Pembelajaran Audio Berbasis Podcast Berbantuan Aplikasi Spotify pada Pelajaran IPS di SMP IT Nurul Ishlah Banda Aceh - Vathin Asyura Putri; Sakdiyah Sakdiyah; Muhjam Kamza (Jurnal Tunas Pendidikan, 2023)
Many learning media can be applied in the learning environment, especially for schools that are already available facilities and infrastructure can be utilised audio media made to provide flexible learning facilities. This study aims to determine the process of applying podcast-based audio learning media assisted by the spotify application in social studies lessons at SMP IT Nurul Ishlah Banda Aceh. Then to find out the student response to the application of podcast-based audio learning media assisted by spotify application in social studies lessons at SMP IT Nurul Ishlah Banda Aceh. This research uses a qualitative approach with descriptive research type. The subjects in this study were all students of class VIII-2, totalling 26 students. Data collection techniques in this study include observation, questionnaires, interviews, and documentation. Based on the results of the research conducted, it can be seen that (1) The application of podcast-based audio learning media assisted by the spotify application in social studies lessons at SMP IT Nurul Ishlah Banda Aceh has been carried out well in accordance with the steps of media application and the syntax of the learning model used, namely problem solving. This can be seen from the results of the analysis of the application of learning media obtained an average value of 85.4% and entered into good criteria. (2) The response of students of class VIII-2 SMP IT Nurul Ishlah Banda Aceh in the application of audio learning media is good.